Report on Candidates' Work in the Secondary Education Certificate Examination June 1992: Home Economics-Management - Caribbean Examinations Council (CXC, 1992)
This report provides general and detailed comments on the performance of candidates in the June 1992 Caribbean Secondary Education Certificate (CSEC) general and basic proficiency examinations in Home Economics-Management.
Keywords: CXC CSEC examinations